Deposited poly-Si as on-demand linewidth compensator for on-chip Fabry-Perot interferometer and vertical linear variable optical filter bandpass and passband manipulation - Goh, Simon Chun Kiat (2021)
Deep reactive ion etching (DRIE) is an important process for etching vertical structures for microelectromechanical systems. Due to the sidewall profile of some photoresists as well as effects from upstream processes, bulk micromachined structures, to a certain extent, could differ from expected. Concerning photonics applications, minute deviations from the intended design might alter its optical characteristics. The most popular approach is to introduce a compensation factor during mask design. However, such a method is not robust enough to accommodate batch variations due to varying process conditions. In one particular example specific to this work, the simulated passband for a Si-air Fabry–Perot interferometer configuration was 3.67 μm. However, post DRIE the passband was measured to be 3.40 μm. To resolve this discrepancy, linewidth compensation using low-pressure chemical vapor deposition (LPCVD) poly-Si is presented. When 170 and 194 nm of poly-Si were separately deposited, the passbands redshifted to 3.54 and 3.57 μm, respectively. With the LPCVD poly-Si layer being highly conformable, the full width half maximum remains unchanged at 80 nm. An on-chip linear variable optical filter was demonstrated with a compensation of 194 nm poly-Si. It was observed that the working range redshifted from 3.0–3.9 μm to 3.3–4.5 μm.